2017
DOI: 10.4038/cjs.v46i1.7419
|View full text |Cite
|
Sign up to set email alerts
|

Influence of substrates on the nutritional quality of Pleurotus pulmonarius and Pleurotus ostreatus

Abstract: This investigation is aimed at determining the influence of agro-wastes as substrates on the nutritional quality of Pleurotus pulmonarius and Pleurotus ostreatus. Cassava peels, banana leaves and amended sawdust (sawdust mixed with rice bran in ratio 4:1) were used as growth substrates. Proximate and mineral analyses were carried out using DA 7250 NIR Analyzer and Atomic Absorption of Spectrophotometer machine (AA320N). Both species in amended sawdust had the highest stipe length and pileus diameter of the fru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 11 publications
1
11
0
1
Order By: Relevance
“…It has been suggested that BE should be at least 50 % for a profitable cultivation for Pleurotus species [30]. In this work, the highest BE values were obtained in substrates formulated with WS (up to 43:55 % in strain 129, and up to 72:45 % in strain A01), in accordance with previous reports in this genus [3,5,31,32]. It should be noted that although WS is an abundant and low-cost lignocellulosic residue in the Argentine Pampas region [4], it is of limited availability in Patagonia, and is commercialized principally as livestock.…”
Section: Discussionsupporting
confidence: 91%
“…It has been suggested that BE should be at least 50 % for a profitable cultivation for Pleurotus species [30]. In this work, the highest BE values were obtained in substrates formulated with WS (up to 43:55 % in strain 129, and up to 72:45 % in strain A01), in accordance with previous reports in this genus [3,5,31,32]. It should be noted that although WS is an abundant and low-cost lignocellulosic residue in the Argentine Pampas region [4], it is of limited availability in Patagonia, and is commercialized principally as livestock.…”
Section: Discussionsupporting
confidence: 91%
“…Some authors have also observed a change in the nutritional composition according to the substrate, for both Pleurotus pulmonarius and P. ostreatus (Garuba et al, 2017).…”
Section: Discussionmentioning
confidence: 96%
“…As reported by Raman et al [50], the protein content in P. ostreatus may depend on many factors. The significant influence of the kind of cultivation substrate on the protein content in P. ostreatus fruiting bodies was noticed by many researchers [72,74,93,94]. Hoa et al [58] reported that the differences in the protein content of P. ostreatus fruiting bodies could be due to the varying nitrogen content of substrates.…”
Section: Discussionmentioning
confidence: 99%
“…is related to a number of factors, which may act individually or have interactive effects among them [42,43,71]. In many studies, remarkable variations have been observed in the nutritional contents of P. ostreatus grown on different substrates [72][73][74][75]. Generally, wheat straw is used as the main substrate for P. ostreatus commercial cultivation [13]; however, there is a growing interest in highly available low-cost alternative materials [76][77][78][79].…”
Section: Introductionmentioning
confidence: 99%